2022
DOI: 10.3389/fpsyg.2022.873140
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Green Entrepreneurial Intention: Why Does Sustainability Awareness Matter Among University Students?

Abstract: Entrepreneurship is an essential aspect of economic growth because of its contribution to people’s welfare through employment opportunities. Universities offer compulsory entrepreneurship subjects for students with the support of government policies. Therefore, this study aimed to determine the factors that influence the students’ intentions to become green entrepreneurs using contextual aspects as moderators. The applied theoretical model was the planned behavior (TPB) that adds cultural values and cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 112 publications
(154 reference statements)
1
18
1
Order By: Relevance
“…However, in the extant literature, attitude toward sustainability is analyzed as an essential factor of entrepreneurial intention (do Paço et al , 2011; Schwartz, 2009), and value priorities shape attitude toward sustainability in terms of entrepreneurial intentions (Fischer and Schwartz, 2011). Moreover, our findings are in contradiction with those of Mykolenko et al (2022) and Nguyen et al (2022) but confirm the results reached by Prabowo et al (2022). Shepherd et al (2013) suggested that arguments may be found in high entrepreneurial self-efficacy and high scarcity of industry resources.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…However, in the extant literature, attitude toward sustainability is analyzed as an essential factor of entrepreneurial intention (do Paço et al , 2011; Schwartz, 2009), and value priorities shape attitude toward sustainability in terms of entrepreneurial intentions (Fischer and Schwartz, 2011). Moreover, our findings are in contradiction with those of Mykolenko et al (2022) and Nguyen et al (2022) but confirm the results reached by Prabowo et al (2022). Shepherd et al (2013) suggested that arguments may be found in high entrepreneurial self-efficacy and high scarcity of industry resources.…”
Section: Discussioncontrasting
confidence: 61%
“…Attitudes toward entrepreneurship were found to be positively related to entrepreneurial intention by Nguyen et al (2022), but depending on the cultural context, attitudes may or may not influence entrepreneurial decisions, as concluded by Mykolenko et al (2022). This is the case of a study conducted on Indonesian students, whereby attitudes toward green entrepreneurship were not found to be related to green entrepreneurial intentions (Prabowo et al , 2022). It has been recognized that under high entrepreneurial self-efficacy and high scarcity of industry resources, individuals do not adhere to their pro-environmental values when assessing the environmental damage caused by taking advantage of opportunities (Shepherd et al , 2013).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 98%
“…EE forms EIs by generating the motivation to perceive new opportunities and the adequacy of the means needed to meet entrepreneurial requirements [71,[85][86][87][88]. EE enables college students to enhance the perception of individual and collective entrepreneurial efficiency and feasibility, thus improving entrepreneurial attitude and EI [2,17,49,[59][60][61][62][63][64][65].…”
Section: Theoretical Foundationsmentioning
confidence: 99%
“…The theory of planned behavior combines the attitude of behavior, the feeling of social pressure, and the perception of behavioral control into individual intention [89,90]. According to the theory of planned behavior, EE also improves college students' understanding and control of self-behavior and external pressure, thus enhancing their EI [12,25,34,64,[66][67][68][69][70][71][72].…”
Section: Theoretical Foundationsmentioning
confidence: 99%
See 1 more Smart Citation